MINAT DAN KONSEP DIRI TERHADAP PRESTASI BELAJAR SOSIOLOGI - Astuti Yati; Tudjung Tudjung (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2019)
The research aims to determine the effect of interest on sociology learning achievement, to determine the effect of self-concept on sociology learning The study was conducted by survey method. The population is class XI IPS students of SMA Negeri in Bekasi City with a sample of 60 students and with proportional random sampling technique. Data collection was carried out by distributing questionnaires directly to respondents. This research was conducted in September - October. The results showed: There was a significant influence of self-interest and self-concept on sociology learning achievement of high school students in Bekasi City. This is evidenced by the acquisition of Sig. 0,000 < 0.05 and Fcount = 9,376. Interest and learning motivation variables contributed 24.8% to the sociology learning achievement variable. There is a significant influence of interest in sociology learning achievement of high school students in Bekasi City. This is evidenced by the acquisition of Sig. 0,000 < 0.05 and tcount = 3.821. Interest variable contributed 16.67% in improving sociology learning achievement. There is a significant influence of self-concept on sociology learning achievement of high school students in Bekasi City.